Anti-inflammatory celastrol promotes a switch from leukotriene biosynthesis to formation of specialized pro-resolving lipid mediators - Pace, Simona; Zhang, Kehong; Jordan, Paul M.; Bilancia, Rossella; Wang, Wenfei; Börner, Friedemann; Hofstetter, Robert K.; Potenza, Marianna; Kretzer, Christian; Gerstmeier, Jana; Fischer, Dagmar; Lorkowski, Stefan; et al. (Pharmacological research, 2021)
The pentacyclic triterpenoid quinone methide celastrol (CS) from Tripterygium wilfordii Hook. F. effectively ameliorates inflammation with potential as therapeutics for inflammatory diseases. However, the molecular mechanisms underlying the anti-inflammatory and inflammation-resolving features of CS are incompletely understood. Here we demonstrate that CS potently inhibits the activity of human 5-lipoxygenase (5-LOX), the key enzyme in pro-inflammatory leukotriene (LT) formation, in cell-free assays with IC50 = 0.19–0.49 µM. Employing metabololipidomics using ultra-performance liquid chromatography coupled to tandem mass spectrometry in activated human polymorphonuclear leukocytes or M1 macrophages we found that CS (1 µM) potently suppresses 5-LOX-derived products without impairing the formation of lipid mediators (LM) formed by 12-/15-LOXs as well as fatty acid substrate release. Intriguingly, CS induced the generation of 12-/15-LOX-derived LM including the specialized pro-resolving mediator (SPM) resolvin D5 in human M2 macrophages. Finally, intraperitoneal pre-treatment of mice with 10 mg/kg CS strongly impaired zymosan-induced LT formation and simultaneously elevated the levels of SPM and related 12-/15-LOX-derived LM in peritoneal exudates, spleen and plasma in vivo. Conclusively, CS promotes a switch from LT biosynthesis to formation of SPM which may underlie the anti-inflammatory and inflammation-resolving effects of CS, representing an interesting pharmacological strategy for intervention with inflammatory disorders.
CRIS-Team Scopus Importer:2021-04-19
Keywords: 5-lipoxygenase; arachidonic acid (PubChem CID: 444899); Celastrol; celastrol (PubChem CID: 122724); celecoxib (PubChem CID: 2662); dimethyl sulfoxide (PubChem CID: 679); indomethacin (PubChem CID: 3715); Inflammation; Leukotriene; MK886 (PubChem CID: 3651377); resolvin D5 (PubChem CID: 16061139); Specialized pro-resolving mediators; zileuton (PubChem CID: 60490); zymosan (PubChem CID: 64689)